Cyclical Patterns Affect Microbial Dynamics in the Water Basin of a Nuclear Research Reactor - Van Eesbeeck, Valérie; Props, Ruben; Mysara, Mohamed; Petit, Pauline C. M.; Rivasseau, Corinne; Armengaud, Jean; Monsieurs, Pieter; Mahillon, Jacques; Leys, Natalie (Frontiers in Microbiology, 2021)
The BR2 nuclear research reactor in Mol, Belgium, runs in successive phases of operation (cycles) and shutdown, whereby a water basin surrounding the reactor vessel undergoes periodic changes in physico-chemical parameters such as flow rate, temperature, and radiation. The aim of this study was to explore the microbial community in this unique environment and to investigate its long-term dynamics using a 16S rRNA amplicon sequencing approach. Results from two sampling campaigns spanning several months showed a clear shift in community profiles: cycles were mostly dominated by two Operational Taxonomic Units (OTUs) assigned to unclassified Gammaproteobacterium and Pelomonas, whereas shutdowns were dominated by an OTU assigned to Methylobacterium. Although 1 year apart, both campaigns showed similar results, indicating that the system remained stable over this 2-year period. The community shifts were linked with changes in physico-chemical parameters by Non-metric Multidimensional Scaling (NMDS) and correlation analyses. In addition, radiation was hypothesized to cause a decrease in cell number, whereas temperature had the opposite effect. Chemoautotrophic use of H2 and dead cell recycling are proposed to be used as a strategies for nutrient retrieval in this extremely oligotrophic environment.